Nicotine increases alcohol self‐administration in male rats via a μ‐opioid mechanism within the mesolimbic pathway. (14th August 2020) - Domi, Esi; Xu, Li; Pätz, Marvin; Nordeman, Anton; Augier, Gaëlle; Holm, Lovisa; Toivainen, Sanne; Augier, Eric; Hansson, Anita C.; Heilig, Markus
Abstract : Background and Purpose: Alcohol and nicotine use disorders are commonly comorbid. Both alcohol and nicotine can activate opioid systems in reward‐related brain regions, leading to adaptive changes in opioid signalling upon chronic exposure. The potential role of these adaptations for comorbidity is presently unknown. Here, we examined the contribution of μ and κ‐opioid receptors to nicotine‐induced escalation of alcohol self‐administration in rats. Experimental Approach: Chronic nicotine was tested on alcohol self‐administration and motivation to obtain alcohol. We then tested the effect of the κ antagonist CERC‐501 and the preferential μ receptor antagonist naltrexone on basal and nicotine‐escalated alcohol self‐administration. To probe μ or κ receptor adaptations, receptor binding and G‐protein coupling assays were performed in reward‐related brain regions. Finally, dopaminergic activity in response to alcohol was examined, using phosphorylation of DARPP‐32 in nucleus accumbens as a biomarker. Key Results: Nicotine robustly induced escalation of alcohol self‐administration and motivation to obtain alcohol. This was blocked by naltrexone but not by CERC‐501. Escalation of alcohol self‐administration was associated with decreased DAMGO‐stimulated μ receptor signalling in the ventral tegmental area (VTA) and decreased pDARPP‐32 in the nucleus accumbens shell in response to alcohol. Conclusions and Implications: Collectively, these results suggest that nicotine contributes to escalate alcohol self‐administration through a dysregulation of μ receptor activity in the VTA. These data imply that targeting μ rather than κ receptors may be the preferred pharmacotherapeutic approach for the treatment of alcohol use disorder when nicotine use contributes to alcohol consumption.